2009
DOI: 10.1021/ef9003818
|View full text |Cite
|
Sign up to set email alerts
|

Alga-Based Biodiesel Production and Optimization Using Sugar Cane as the Feedstock

Abstract: The alga Chlorella protothecoides is known to produce oil suitable for biodiesel preparation by heterotrophic cultivation in media containing glucose as a carbon source. In this study, sugar cane juice was used as alternative carbon supply for oil production. As a result, the highest oil content of 53.0% by cell dry weight was achieved. Fermentation in a 5 L bioreactor showed that algae using sugar cane juice hydrolysate (SCH) grow faster than that using glucose. Conversion ratios of sugar/biomass and sugar/oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 18 publications
2
47
0
3
Order By: Relevance
“…Many reports have shown that photoautotrophic and heterotrophic culture conditions result in different biomass and lipid yields for the same microalga strain (Xu et al 2006;Cheng et al 2009). Chlorella emersonii and C. protothecoides gave the highest average lipid and biomass yield among many strains of microalgae tested (Suali and Sarbatly 2012).…”
Section: Microalgae With Heterotrophic Metabolismmentioning
confidence: 99%
“…Many reports have shown that photoautotrophic and heterotrophic culture conditions result in different biomass and lipid yields for the same microalga strain (Xu et al 2006;Cheng et al 2009). Chlorella emersonii and C. protothecoides gave the highest average lipid and biomass yield among many strains of microalgae tested (Suali and Sarbatly 2012).…”
Section: Microalgae With Heterotrophic Metabolismmentioning
confidence: 99%
“…Available online 30 October 2014 high latitudes. However, the addition of organic carbon to the culture medium could significantly impact the operational cost, constituting between 35% and 80% of the medium price depending on the choice of carbon source (Cheng et al 2009;X. Li et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…From this, comes the need for effective options to replace these fuels with viable alternatives that are renewable, clean, inexpensive and sustainable. Several plant-based materials have been tested, including corn, soy, canola and palm oil, among others (Chisti 2007, Cheng et al 2009). …”
Section: Introductionmentioning
confidence: 99%